Computational ethnography: A view from sociology. Issue 1 (January 2022) - Brooker, Phillip
This commentary elaborates on the ideas and projects outlined in this special issue, from a specifically sociological perspective. Much recent work in sociology proposes 'methods mashups' of ethnography and digital data/computational tools in different and diverse ways. However, typically, these have taken the form of applying (with or without tweaks) the principles of ethnography to new domains and data types, as if ethnography itself is stable and immutable; that it has a universal set of methodological principles that unify ethnographic practice. Returning to anthropology (whence, arguably, ethnography originally came) is, therefore, a useful way to extend our methodological thinking to (re)consider what ethnography is and how it operates, and from there think more clearly about how it may be effectively combined with digital data/computational tools in an emerging 'Computational Anthropology'.